Magnetically-expanded self-fastening anchor rod material and preparation method thereof

By using magneto-expanded self-tightening anchor material in anchor support, the self-expanding and self-tightening is achieved using magnetic field, the problem of increasing anchor agent is solved, and the effect of simple process, low cost and outstanding reinforcement effect is achieved.

CN119737179AActive Publication Date: 2025-04-01CCTEG COAL MINING RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411865421.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

During the anchor support process, the anchoring agent needs to be added to the additional process, which increases the labor intensity of workers, seriously affects the application of anchor support.

Method used

Magnetic expansion self-tightening anchor material is used, which consists of anchor matrix monomer material, initiator, anchor matrix crosslinking agent, reinforcer, magnetic molecules and interface modifier. Self-expanding self-tightening is achieved by applying a magnetic field outside, reducing dependence on anchor agent.

Benefits of technology

The self-tightening effect with simple process and low cost is achieved, which reduces the process, reduces the cost, and significantly improves the reinforcement effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119737179A_ABST
    Figure CN119737179A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic expansion self-fastening anchor rod material and a preparation method thereof. The magnetic expansion self-fastening anchor rod material comprises the following components in parts by mass: 90-100 parts of an anchor rod matrix monomer material, 1 part of an initiator, 5-8 parts of an anchor rod matrix cross-linking agent, 1-2 parts of an anchor rod matrix cross-linking accelerant, 1-3 parts of a reinforcing agent, 20-30 parts of magnetic molecules and 3-5 parts of an interface modifier. According to the self-fastening anchor rod material, self-expansion and self-fastening can be achieved only by applying a magnetic field to the outside, an anchoring agent does not need to be additionally added, the working procedures are reduced, the cost is reduced, and the reinforcing effect is outstanding. The invention further provides a preparation method of the self-fastening anchor rod material. The preparation method has the advantages of being simple in process, low in cost and easy to apply and popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new anchor rod materials, and in particular to a magneto-expansive self-tightening anchor rod material and a preparation method thereof. Background Art

[0002] With the increase in the depth of coal mining, the surrounding rock of coal mine tunnels undergoes continuous expansion deformation and sustained deformation under the effects of deep wells, looseness, crushing, and impact. Anchor support is an effective means to solve the problem of tunnel deformation. Anchor support needs to work together with anchors and anchoring agents. Anchors enhance adhesion by chemically reacting with the base material. Anchors can also enhance adhesion through physical action, by generating friction with the base material or by relying on physical structures (such as protrusions, grooves, or mesh structures). The use of anchors and anchors effectively improves the integrity and stability of the tunnel surrounding rock, and has achieved good control effects. However, in the use of anchors and anchors, anchors require additional processes, which increases the labor intensity of workers and seriously affects the application of anchor support. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application proposes a magnetic expansion self-tightening anchor material and a preparation method thereof, wherein the preparation method has the characteristics of simple process, low cost and easy promotion and application; the self-tightening anchor material provided by the present application can achieve self-expansion and self-tightening only by applying a magnetic field externally, and there is no need to add an additional anchoring agent in a disordered manner, which reduces the process, reduces the cost and has an outstanding reinforcement effect.

[0004] According to an embodiment of the first aspect of the present application, a magneto-expandable self-tightening anchor material is proposed, comprising the following components in parts by mass: 90-100 parts of anchor matrix monomer material, 1 part of initiator, 5-8 parts of anchor matrix cross-linking agent, 1-2 parts of anchor matrix cross-linking promoter, 1-3 parts of enhancer, 20-30 parts of magnetic molecules, and 3-5 parts of interface modifier.

[0005] In some embodiments, the anchor matrix monomer material includes butadiene, clethodim, methyl 2,4-pentadienoate and 2-ethyl-1,3-butadiene in a mass ratio of 1:3:2:2.

[0006] In some embodiments, the initiator comprises benzoyl peroxide.

[0007] In some embodiments, the anchor matrix crosslinking agent includes a 2,5-mercapto-1,3,4-thiadiazole-sulfur dichloride polymer and a zinc propylene bisdithiocarbamate polymer in a mass ratio of 6:1.

[0008] In some embodiments, the anchor matrix cross-linking promoter includes 5-[(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thionothiazolidine-3-acetic acid and 5-[1-methyl-2-(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thionothiazolidine-3-acetic acid in a mass ratio of 5:1.

[0009] In some embodiments, the reinforcing agent includes 1,3,5,7,9,11,14-heptacyclohexyltricyclo[7.3.3.15,11]heptasiloxane-3,7,14-triol and N-phenylamino-cage polysilsesquioxane in a mass ratio of 1:1.

[0010] In some embodiments, the magnetic molecules include ferrocenecarboxaldehyde, ferroceneacetylene, hydroxymethylferrocene, and ferrocenecarboxylic acid in a mass ratio of 1:1:4:2.

[0011] In some embodiments, the interface modifier includes octylphenoxy polyethoxy ethyl phosphate and perfluorooctane sulfonic acid amine in a mass ratio of 3:1.

[0012] According to an embodiment of the second aspect of the present application, a method for preparing a magneto-expansion self-tightening anchor material is provided, comprising the following steps:

[0013] Mixing the anchor matrix monomer material, the reinforcing agent, the magnetic molecule, and the interface modifier according to the stoichiometric ratio to obtain a mixed matrix material;

[0014] Adding an initiator, an anchor matrix crosslinking agent, and an anchor matrix crosslinking accelerator to the mixed matrix material according to stoichiometric amounts and mixing them evenly to obtain a mixture A;

[0015] The mixed material A is heated and melted to perform a polymerization reaction; the melted slurry is injected into a mold and heated to 150-180° C. to perform a cross-linking reaction to obtain the self-tightening anchor material described in any of the above embodiments.

[0016] In some embodiments, the mixture A is heated to 100-120°C to undergo polymerization; the melted slurry is heated to 25-30W / cm 2 Ultrasonic heating.

[0017] The present invention uses an olefin with multiple carbon-carbon double bonds as an anchor rod matrix material, adds a magnetic expansion material thereto, and then polymerizes and crosslinks under the action of an initiator, an anchor rod matrix crosslinking agent, and an anchor rod matrix crosslinking promoter to prepare a magnetic expansion self-tightening anchor rod material. Finally, a magnetic expansion self-tightening anchor rod material with a simple preparation method, low cost, and outstanding reinforcement effect is developed and promoted for application.

[0018] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0020] Figure 1 It is a flow chart of a method for preparing a self-tightening anchor material proposed in one embodiment of the present application. DETAILED DESCRIPTION

[0021] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0022] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0024] To achieve the above-mentioned purpose, according to an embodiment of the first aspect of the present application, a magneto-expandable self-tightening anchor material is proposed, comprising the following components in parts by mass: 90-100 parts of anchor matrix monomer material, 1 part of initiator, 5-8 parts of anchor matrix cross-linking agent, 1-2 parts of anchor matrix cross-linking promoter, 1-3 parts of enhancer, 20-30 parts of magnetic molecules, and 3-5 parts of interface modifier.

[0025] In this embodiment, the self-tightening anchor material includes 90-100 parts by weight of anchor matrix monomer material, wherein the anchor matrix monomer material includes butadiene (CAS: 106-99-0), clethodim (CAS: 99129-21-2), methyl 2,4-pentadienoate (CAS: 1515-75-9), and 2-ethyl-1,3-butadiene (CAS: 3404-63-5) in a mass ratio of 1:3:2:2. In some embodiments, the mass fraction of the anchor matrix monomer material is 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts, or 100 parts. If the mass fraction of the anchor matrix monomer material is small, such as less than 90 parts, the self-tightening anchor material has a low molecular weight and insufficient mechanical strength. If the number of monomer materials in the anchor rod matrix is ​​large, such as greater than 100 parts, there will be a large amount of residual monomers that have not been polymerized, which will affect the mechanical strength of the self-tightening anchor rod material.

[0026] In this embodiment, the self-tightening anchor material includes 1 part by weight of an initiator, and the initiator includes benzoyl peroxide.

[0027] In this embodiment, the self-tightening anchor material includes 5-8 parts by weight of an anchor matrix crosslinking agent, wherein the anchor matrix crosslinking agent includes 2,5-mercapto-1,3,4-thiadiazole-dichloride sulfur polymer (CAS: 174672-51-6) and propylene bis dithiocarbamate zinc polymer (CAS: 9016-72-2) in a mass ratio of 6:1. In some embodiments, the mass fraction of the anchor matrix crosslinking agent is 5 parts, 6 parts, 7 parts or 8 parts, etc. If the mass fraction of the anchor matrix crosslinking agent is small, such as less than 5 parts, the crosslinking density of the self-tightening anchor material is low, and the mechanical strength and flexibility are affected. If the mass fraction of the anchor matrix crosslinking agent is large, such as greater than 8 parts, there is residual unreacted crosslinking agent, which affects the mechanical strength of the self-tightening anchor material.

[0028] In this embodiment, the self-tightening anchor material includes 1-2 parts by weight of an anchor matrix cross-linking promoter, wherein the anchor matrix cross-linking promoter includes 5-[(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thioketothiazolidine-3-acetic acid (CAS: 65152-09-2) and 5-[1-methyl-2-(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thioketothiazolidine-3-acetic acid (CAS: 25651-76-7) in a mass ratio of 5:1. In some embodiments, the mass fraction of the anchor matrix cross-linking promoter is 1 part or 2 parts, etc. If the mass fraction of the anchor matrix cross-linking promoter is small, such as less than 1 part, the cross-linking effect is not good, which affects the tensile strength and deformation resistance of the self-tightening anchor material. If the amount of anchor matrix cross-linking promoter is large, such as more than 2 parts, the local cross-linking rate is fast, the system cross-linking is uneven, and phase separation is formed, which affects the durability of the self-tightening anchor material.

[0029] In this embodiment, the self-tightening anchor material includes a reinforcing agent in an amount of 1-3 parts by mass, wherein the reinforcing agent includes 1,3,5,7,9,11,14-heptacyclohexyl tricyclo[7.3.3.15,11]heptasiloxane-3,7,14-triol (CAS: 47904-22-3) and N-phenylamino-cage polysilsesquioxane (CAS: 1187675-16-6) in a mass ratio of 1:1. In some embodiments, the reinforcing agent has an amount of 1, 2 or 3 parts by mass, and the reinforcing agent acts as a nano-crosslinking point to enhance the crosslinking and curing of the anchor matrix, thereby significantly improving the mechanical strength of the anchor material. If the amount of the reinforcing agent is small, such as less than 1 part, the reinforcing effect is not good, and the tensile strength and rigidity of the self-tightening anchor material are insufficient. If the amount of the reinforcing agent is large, such as greater than 3 parts, the self-tightening anchor material has high rigidity, but insufficient flexibility and impact resistance, and is prone to rupture during use.

[0030] In this embodiment, the self-tightening anchor material includes 20-30 parts by mass of magnetic molecules, wherein the magnetic molecules include ferrocene formaldehyde (CAS: 12093-10-6), ferrocene acetylene (CAS: 1271-47-2), hydroxymethyl ferrocene (CAS: 1273-86-5) and ferrocene carboxylic acid (CAS: 1271-42-7) in a mass ratio of 1:1:4:2. In some embodiments, the mass fraction of the magnetic molecules is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, etc. If the mass fraction of the magnetic molecules is small, such as less than 20 parts, the magnetic expansion coefficient is insufficient, and the anchoring force of the self-tightening anchor material is not high. If the mass fraction of the magnetic molecules is large, such as greater than 30 parts, the tensile strength and deformation resistance of the anchor of the self-tightening anchor material are not high, and the anchoring effect of the anchor is affected.

[0031] Among them, magnetic expansion materials such as ferrocene formaldehyde, ferrocene acetylene, hydroxymethyl ferrocene, and ferrocene formic acid are added to the anchor rod, so that the anchor rod has magneto-expansion characteristics. In field applications, it only needs to apply a magnetic field externally to achieve self-expansion and self-tightening. The additional anchoring agent is added in a disordered manner, which reduces the process and reduces the cost. In addition, the active functional groups formaldehyde, alkynyl, and formic acid in the magnetic molecules participate in the cross-linking reaction of the anchor rod matrix to form a three-dimensional network structure, which makes the cross-linking degree inside the anchor rod material higher. The cross-linking points between the chains generated by the cross-linking inhibit the sliding between the polymer chains, and the mechanical properties of the anchor rod are improved. When the anchor rod material is subjected to external forces such as impact and collision, it can resist damage, so that the impact resistance of the anchor rod is improved.

[0032] In this embodiment, the self-tightening anchor material includes 3-5 parts by weight of an interface modifier, wherein the interface modifier includes octylphenoxy polyethoxyethyl phosphate (CAS: 52623-95-7) and perfluorooctane sulfonic acid amine (CAS: 29081-56-9) in a mass ratio of 3:1. In some embodiments, the mass fraction of the interface modifier is 3 parts, 4 parts or 5 parts, etc. If the mass fraction of the interface modifier is small, such as less than 3 parts, the interface of the magnetic molecules and the anchor matrix is ​​not tightly bonded, and phase separation is likely to occur, affecting the overall performance of the self-tightening anchor material. If the mass fraction of the interface modifier is large, such as greater than 5 parts, the tensile strength of the anchor of the self-tightening anchor material is affected, and the anchor is broken.

[0033] According to the second aspect of the present application, a method for preparing a magnetic expansion self-tightening anchor material is provided, such as Figure 1 The following steps are involved:

[0034] S1: mixing the anchor matrix monomer material, the reinforcing agent, the magnetic molecule and the interface modifier according to the stoichiometric ratio to obtain a mixed matrix material;

[0035] S2: adding the initiator, the anchor matrix crosslinking agent, and the anchor matrix crosslinking accelerator to the mixed matrix material according to the stoichiometric amount and mixing them evenly to obtain a mixture A;

[0036] S3: heating and melting the mixed material A to carry out a polymerization reaction; injecting the melted slurry into a mold and heating it to 150-180° C. to carry out a cross-linking reaction to obtain the self-tightening anchor material in any of the above embodiments.

[0037] In some embodiments, the mixture A is heated to 100-120°C to undergo polymerization; the molten slurry is heated to 25-30W / cm 2 Ultrasonic heating.

[0038] In step S1, 90-100 parts of anchor matrix monomer material, 1-3 parts of reinforcing agent, 20-30 parts of magnetic molecules, and 3-5 parts of interface modifier are weighed according to mass fractions, and stirred in a dry powder mixer for 30 minutes to uniformly mix, to obtain a mixed matrix material;

[0039] Step S2, weigh 1 part of initiator, 5-8 parts of anchor matrix crosslinking agent, and 1-2 parts of anchor matrix crosslinking accelerator according to their mass parts, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0040] In S3, the mixture A is heated to 100-120° C. to cause a polymerization reaction, wherein in some embodiments, the mixture A is heated to 100° C., 105° C., 110° C., 115° C., 118° C., 120° C.; the molten slurry is injected into a mold of a specific shape and heated at a power density of 25-30 W / cm 2 Ultrasonic heating to 150-180°C causes a cross-linking reaction to prepare the self-tightening anchor material in any of the above embodiments. In some embodiments, the temperature of the cross-linking reaction is 150°C, 160°C, 170°C, 180°C, etc.

[0041] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0042] Example 1

[0043] The present embodiment provides a magneto-expandable self-tightening anchor material, and its preparation method and specific operating parameters are as follows: 91 parts of anchor matrix monomer material, 3 parts of reinforcing agent, 30 parts of magnetic molecules, and 5 parts of interface modifier are weighed according to mass fractions, and stirred in a dry powder mixer for 30 minutes to uniformly mix them to obtain a mixed matrix material.

[0044] Weigh 1 part of initiator, 8 parts of anchor matrix crosslinking agent, and 2 parts of anchor matrix crosslinking accelerator according to their mass parts, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0045] Mixture A is heated to 120°C for polymerization, and then the molten slurry is injected into a mold of a specific shape and heated at a power density of 28W / cm 2 Ultrasonic heating to 160° C. causes a cross-linking reaction, thereby preparing a self-tightening anchor material.

[0046] Example 2

[0047] This embodiment is different from Embodiment 1 in the following aspects: 94 parts of anchor matrix monomer material, 1 part of reinforcing agent, 28 parts of magnetic molecules and 5 parts of interface modifier are weighed by mass, and the mixture is evenly mixed in a dry powder mixer for 30 minutes to obtain a mixed matrix material.

[0048] Weigh 1 part of initiator, 8 parts of anchor matrix crosslinking agent, and 2 parts of anchor matrix crosslinking accelerator according to their mass parts, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0049] Mixture A is heated to 120°C for polymerization, and then the molten slurry is injected into a mold of a specific shape and heated at a power density of 28W / cm 2 Ultrasonic heating to 150°C causes a cross-linking reaction.

[0050] Example 3

[0051] This embodiment is different from Embodiment 1 in the following aspects: 99 parts of anchor matrix monomer material, 1 part of reinforcing agent, 21 parts of magnetic molecules, and 4 parts of interface modifier are weighed by mass, and the mixture is evenly mixed in a dry powder mixer for 30 minutes to obtain a mixed matrix material.

[0052] Weigh 1 part of initiator, 6 parts of anchor matrix crosslinking agent, and 2 parts of anchor matrix crosslinking accelerator according to their mass parts, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0053] Mixture A is heated to 100°C for polymerization, and then the molten slurry is injected into a mold of a specific shape at a power density of 30W / cm 2 Ultrasonic heating to 180°C causes a cross-linking reaction.

[0054] Example 4

[0055] This embodiment is different from Embodiment 1 in the following aspects: 100 parts of anchor matrix monomer material, 2 parts of reinforcing agent, 20 parts of magnetic molecules and 3 parts of interface modifier are weighed by mass, and the mixture is evenly mixed in a dry powder mixer for 30 minutes to obtain a mixed matrix material.

[0056] Weigh 1 part of initiator, 5 parts of anchor matrix crosslinking agent, and 1 part of anchor matrix crosslinking accelerator according to their mass proportions, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0057] Mixture A is heated to 100°C for polymerization, and then the molten slurry is injected into a mold of a specific shape at a power density of 25W / cm 2 Ultrasonic heating to 170°C causes a cross-linking reaction.

[0058] Example 5

[0059] This embodiment is different from Embodiment 1 in the following aspects: 90 parts of anchor matrix monomer material, 2 parts of reinforcing agent, 29 parts of magnetic molecules and 4 parts of interface modifier are weighed by mass, and the mixture is evenly mixed in a dry powder mixer for 30 minutes to obtain a mixed matrix material.

[0060] Weigh 1 part of initiator, 7 parts of anchor matrix crosslinking agent, and 1 part of anchor matrix crosslinking accelerator according to their mass parts, add them to the mixed matrix material, and stir in a dry powder mixer for 20 minutes to obtain a mixture A.

[0061] Mixture A is heated to 110°C for polymerization, and then the molten slurry is injected into a mold of a specific shape at a power density of 25W / cm 2 Ultrasonic heating to 150°C causes a cross-linking reaction.

[0062] Experimental example

[0063] The self-tightening anchor materials in the various embodiments were tested after use, and the results are shown in Table 1.

[0064] Table 1 Performance results of the self-tightening anchor material in the embodiment

[0065]

[0066] It can be seen from the results in Table 1 that the self-tightening anchor material provided by the present application has an excellent magnetic expansion recovery rate and an outstanding reinforcement effect.

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0068] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A magneto-expansion self-tightening anchor material, characterized in that: The invention comprises the following components in parts by weight: 90-100 parts of anchor matrix monomer material, 1 part of initiator, 5-8 parts of anchor matrix crosslinking agent, 1-2 parts of anchor matrix crosslinking accelerator, 1-3 parts of reinforcing agent, 20-30 parts of magnetic molecules and 3-5 parts of interface modifier.

2. The self-tightening anchor material according to claim 1, characterized in that: The anchor rod matrix monomer material comprises butadiene, clethodim, methyl 2,4-pentadienoate and 2-ethyl-1,3-butadiene in a mass ratio of 1:3:2:

2.

3. The self-tightening anchor material according to claim 1, characterized in that: The initiator includes benzoyl peroxide.

4. The self-tightening anchor material according to claim 1, characterized in that: The anchor matrix crosslinking agent comprises a 2,5-mercapto-1,3,4-thiadiazole-sulfur dichloride polymer and a propylene bisdithiocarbamate zinc polymer in a mass ratio of 6:

1.

5. The self-tightening anchor material according to claim 1, characterized in that: The anchor matrix cross-linking promoter comprises 5-[(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thioketothiazolidine-3-acetic acid and 5-[1-methyl-2-(3-methylthiazolidine-2-ylidene)ethylidene]-4-oxo-2-thioketothiazolidine-3-acetic acid in a mass ratio of 5:

1.

6. The self-tightening anchor material according to claim 1, characterized in that: The reinforcing agent comprises 1,3,5,7,9,11,14-heptacyclohexyltricyclo[7.3.3.15,11]heptasiloxane-3,7,14-triol and N-phenylamino-cage polysilsesquioxane in a mass ratio of 1:

1.

7. The self-tightening anchor material according to any one of claims 1 to 6, characterized in that: The magnetic molecules include ferrocenecarboxaldehyde, ferroceneacetylene, hydroxymethylferrocene and ferrocenecarboxylic acid in a mass ratio of 1:1:4:

2.

8. The self-tightening anchor material according to claim 7, characterized in that: The interface modifier comprises octylphenoxy polyethoxy ethyl phosphate and perfluorooctane sulfonic acid amine in a mass ratio of 3:

1.

9. A method for preparing a magneto-expansion self-tightening anchor material, characterized in that: The following steps are involved: Mixing the anchor matrix monomer material, the reinforcing agent, the magnetic molecule, and the interface modifier according to the stoichiometric ratio to obtain a mixed matrix material; Adding an initiator, an anchor matrix crosslinking agent, and an anchor matrix crosslinking accelerator to the mixed matrix material according to stoichiometric amounts and mixing them evenly to obtain a mixture A; The mixed material A is heated and melted to carry out a polymerization reaction; the melted slurry is injected into a mold and heated to 150-180° C. to carry out a cross-linking reaction, so as to prepare the self-tightening anchor material according to any one of claims 1-8.

10. The preparation method according to claim 9, characterized in that: The mixed material A is heated to 100-120°C to undergo polymerization reaction; the melted slurry is heated to 25-30W / cm 2 Ultrasonic heating.

Citation Information

Patent Citations

  • Method for installation of medicine volume anchor bar anchorage agent

    CN101250876A

  • Wading tower foundation and construction method

    CN117286903A

  • Anchoring-agent-free self-fastening glass fiber reinforced plastic anchor rod with shape memory performance and preparation method and application thereof

    CN118325293A

  • electromagnetic actuator.

    NL1017356A